The connection between Trypanosoma cruzi transmission cycles by Triatoma brasiliensis brasiliensis: A threat to human health in an area susceptible to desertification in the Seridó, Rio Grande do Norte, Brazil - Vanessa Lima-Neiva; Helena Keiko Toma; Lúcia Maria Abrantes Aguiar; Catarina Macedo Lopes; Letícia Paschoaletto Dias; Teresa Cristina Monte Gonçalves; Jane Costa (Public Library of Science (PLoS), 2021)
An outbreak of Chagas disease, possibly involving its vector Triatoma brasiliensis brasiliensis, was identified in the state of Rio Grande do Norte (RN). Given the historical significance of this vector in public health, the study aimed to evaluate its role in the transmission dynamics of the protozoan Trypanosoma cruzi in an area undergoing desertification in the Seridó region, RN, Brazil. We captured triatomines in sylvatic and anthropic ecotopes. Natural vector infection was determined using parasitological and molecular methods and we identified discrete typing units (DTUs) of T. cruzi by analyzing the COII gene of mtDNA, 24Sα rDNA, and mini-exon gene. Their blood meals sources were identified by amplification and sequencing of the mtDNA cytochrome b gene. A total of 952 T. b. brasiliensis were captured in peridomestic (69.9%) and sylvatic ecotopes (30.4%). A wide range of natural infection rates were observed in peridomestic (36.0% - 71.1%) and sylvatic populations (28.6% - 100.0%). We observed the circulation of TcI and TcII DTUs with a predominance of Tcl in sylvatic and peridomestic environments. Kerodon rupestris, rocky cavy (13/39), Homo sapiens, human (8/39), and Bos taurus, ox (6/39) were the most frequently detected blood meals sources. Thus, Triatoma b. brasiliensis is invading and colonizing the human dwellings. Furthermore, high levels of natural infection, coupled with the detection of TcI and TcII DTUs, and also the detection of K. rupestris and H. sapiens as blood meals sources of infected T. b. brasiliensis indicate a risk of T. cruzi transmission to human populations in areas undergoing desertification. Author summary Chagas disease currently affects about six to seven million people worldwide, resulting in high morbidity, mortality, and economic burden in endemic countries of Latin America. Its etiological agent, Trypanosoma cruzi, circulates among a wide variety of mammalian and insect vectors. Triatoma brasiliensis brasiliensis is adapted to the dry and warm climate of the Caatinga biome, and is considered the main vector in the semi-arid areas of northeastern Brazil. Information on the infestation, natural infection rates, T. cruzi strains, and blood meals sources of this vector is crucial for understanding the dynamics of T. cruzi transmission in areas susceptible to desertification. Triatoma b. brasiliensis colonizes peridomestic structures, particularly in the stone walls of cattle corrals that emerge as a refuge for sylvatic populations where they access a variety of blood meals sources. The predominance of the TcI strain in the sylvatic and peridomestic environments shows an overlap of transmission cycles by T. cruzi mediated by T. b. brasiliensis. The high rates of natural infection and the evidence of their feeding on humans and the rodent K. rupestris are worrisome and indicate the threat this vector poses to human health in the area studied.